2006
DOI: 10.1017/s0025315406013580
|View full text |Cite
|
Sign up to set email alerts
|

A new Mediterranean ‘lithistid’ sponge, Aciculites mediterranea sp. nov. (Porifera: Demospongiae) from a dark marine cave in Sardinia

Abstract: A first record of the genus Aciculites in the Mediterranean Sea and the description of Aciculites mediterranea sp. nov. are here presented from a faunistic survey in a dark shallow marine cave of the north-western Sardinian karstic area. The new species is characterized by a massive cerebellum-like growth form, and a peculiar distribution of inhalant and exhalant areas, respectively, in depressed and elevated portions of the sponge surface. Oscules show a long narrow atrial cavity. Ectosomal skeleton is made o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 5 publications
4
18
0
1
Order By: Relevance
“…The existence of species with disjunct distributions in distant marine caves raises questions about how these species can keep their metapopulation dynamics. It has been suggested that a stepping stones model, with larvae moving passively from one cryptic habitat to another, was plausible for some cases (Manconi et al 2006(Manconi et al , 2009. Recent discoveries highlight that these cave-exclusive species are often deepwater species that have denser populations in bathyal areas but are also able to colonize shallow cavernicolous habitats (Bakran-Petricioli et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The existence of species with disjunct distributions in distant marine caves raises questions about how these species can keep their metapopulation dynamics. It has been suggested that a stepping stones model, with larvae moving passively from one cryptic habitat to another, was plausible for some cases (Manconi et al 2006(Manconi et al , 2009. Recent discoveries highlight that these cave-exclusive species are often deepwater species that have denser populations in bathyal areas but are also able to colonize shallow cavernicolous habitats (Bakran-Petricioli et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…One of the particularities of these caves is a common occurrence of lithistid sponges. Lithistid sponges are rare in the Mediterranean Sea and only 9 species of 9 genera have been reported so far (see detailed review in Manconi et al, 2006;Manconi and Serusi, 2008, and references herein). Those cited from submarine caves are even less common and are poorly studied.…”
Section: Introductionmentioning
confidence: 99%
“…Those cited from submarine caves are even less common and are poorly studied. Only six lithistid species of six genera were reported from submarine caves: these are Discodermia polydiscus (Bowerbank, 1869) (Theonellidae Lendenfeld, 1903) and Corallistes masoni (Bowerbank, 1869) (Corallistidae Sollas, 1888) from the caves around Marseille (Pouliquen, 1969a(Pouliquen, , b, 1972, Gastrophanella phoeniciensis Perez, Vacelet, Bitar andZibrowius, 2004 (Siphonidiidae Lendenfeld, 1903) and Microscleroderma lamina Perez, Vacelet, Bitar andZibrowius, 2004 (Scleritodermidae Sollas, 1888) from a Lebanese cave (Perez et al, 2004), Aciculites mediterranea Pisera, 2006 (Scleritodermidae Sollas, 1888) from a northern Sardinian cave (Manconi et al, 2006), and Neophrissospongia nana Serusi, 2008 (Corallistidae Sollas, 1888) from a western Sardinian cave. The species Discodermia polydiscus and Coral-listes masoni were also recorded from the deep sea in the bathyal zone (Vacelet, 1969;Magnino et al, 1999, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Nine species belonging to 9 genera of 6 families have been until now recorded in the Mediterranean Sea (Appendix 1) (Topsent 1892a(Topsent , 1893(Topsent , 1925Vacelet 1960Vacelet , 1969Pouliquen 1969Pouliquen , 1972Pulitzer-Finali 1970Pansini 1992Pansini , 1995Boury-Esnault et al 1994;Magnino et al 1999;Pansini and Longo, 2003;Perez et al 2004;Longo et al 2005;Manconi et al 2006;Zibrowius and Taviani 2005). Th e taxonomic richness appears to be notably higher in the tropics (Lévi 1991;Pisera and Lévi 2002;Schlacher-Hoenlinger et al 2005) whereas the low values in the Mediterranean may be explained by the occurrence of extinction phenomena due to harsh environmental/climatic changes during the history of this basin (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…All Mediterranean records refer to genera characterised by a highly disjunct distribution with a spot-like pattern in tropical/subtropical latitudinal ranges of the Atlantic, Indian and western Pacifi c oceans. Th ese taxonomic and biogeographic patterns suggest the condition of lithistids as remnants of an ancient Tethyan fauna (Reid 1967;Perez et al 2004;Manconi et al 2006;Pisera and Vacelet 2006).…”
Section: Introductionmentioning
confidence: 99%